2009
DOI: 10.1093/jjco/hyp087
|View full text |Cite
|
Sign up to set email alerts
|

Fusion of MRI and Sonography Image for Breast Cancer Evaluation Using Real-time Virtual Sonography with Magnetic Navigation: First Experience

Abstract: Our results suggest that the RVS system can identify enhancing breast lesions with excellent accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 31 publications
2
48
0
1
Order By: Relevance
“…In contrast, Narsule et al found a decreased procedure time for the same system [127]. Motion of the target structure is a problem for some percutaneous interventions, mostly due to breathing during punctures [76,126,125,112,91] Improved diagnosis compared to conventional US. [126,125,112] No benefit compared to contrast enhanced sonography.…”
Section: Clinical Evidencementioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, Narsule et al found a decreased procedure time for the same system [127]. Motion of the target structure is a problem for some percutaneous interventions, mostly due to breathing during punctures [76,126,125,112,91] Improved diagnosis compared to conventional US. [126,125,112] No benefit compared to contrast enhanced sonography.…”
Section: Clinical Evidencementioning
confidence: 99%
“…This technique is sometimes used for guidance of punctures without tracking the puncture needle itself, but instead using conventional USguidance for needle insertion. Another possibility is to use this technology for non-invasive diagnosis, such as for breast cancer [126]. Some manufacturers offer such RVS systems that include EM tracking, see Sec.…”
Section: A Range Of Applicationmentioning
confidence: 99%
See 2 more Smart Citations
“…Its first clinical use was reported for analysis of lesions or tumours of the liver [3], breast [4], and prostate [5]. Since then an increasing number of reports have been published, primarily aiming to use a combined image modality approach for improvement of ultrasound-guided biopsies [6].…”
Section: Discussionmentioning
confidence: 99%